Novel synthesis of Cyanoacetylhydrazone Derivaties and their antimicrobial and antioxidant activities - Puah, Perng Yang (2014)
In this study, cyanoacetylhydrazone derivatives that possessing an azometine (NHN=CH-) proton constitute an important class of compounds was synthesized and their biological activities were evaluated. The structures of newly synthesized compounds were confirmed by elemental analysis, mR spectral data. The range of the infrared region used is (4000""'650 cm-l ). All synthesized compounds were tested and evaluated as antimicrobial and antiradical agents. In the determination of antimicrobial activity, the synthesized compounds showed no degree of inhibition against two types of bacterial namely Streptococcus pneumonia (G+) and Escherichia coli (G-) due to low percentage of purity of the synthesized compounds. A disk-diffusion method was use to evaluate the antimicrobial property of those compounds and Kirby-Bour disk-diffusion method was applied with modification. The antioxidant activity of synthesized compounds was determined by l,l-Diphenyl-2-picrylhydrazyl (DPPH) assay. The synthesized compounds showed weaker antiradical activity (higher IC50) than BHT which showed 0.0686 mg/mL.= In conclusion, four types of cyanoacetylhydrazone compounds were synthesized and showed no Inhibition in antimicrobial and lower potential in antioxidant properties. Hence, future study can be carried out to investigate and improve the effectiveness and purity of producing these compounds for better screening biological activities.